Psychosocial approach using storytelling therapy to reduce hospitalization-related anxiety in preschool children - Firdaus Panghegar, Fernando; Khadijah, Siti; Rohaya, Nizla (Palembang MediRose Publisher, 2025)
Background: Anxiety is one of the most common problems experienced by preschool children during hospitalization. This condition is concerning because it may negatively affect the healing process. Play therapy is recognized as an effective strategy to reduce anxiety, yet limited research has examined the use of storytelling therapy, particularly through fables, which provide strong stimulation to alleviate fear and anxiety. Objective: This study aimed to analyze the effect of storytelling play therapy on the anxiety levels of preschool-aged children during hospitalization. Methods: A quasi-experimental design with a one-group pre-test–post-test approach was employed. A purposive sampling technique was used, resulting in a total of 31 preschool participants. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS) observation sheet. Data were analyzed using the Wilcoxon test with IBM SPSS version 26. Results: The mean age of participants was 3.97 years. The average pre-test anxiety score was 25.23, while the average post-test score was 14.61, with a mean reduction of 10.62 points. Hypothesis testing revealed a statistically significant difference (p < 0.001). Conclusion: Storytelling play therapy effectively reduced anxiety among hospitalized preschool children. This intervention may be recommended as a non-pharmacological approach in pediatric nursing practice. Nurses are encouraged to integrate storytelling therapy into hospital services as part of holistic care that addresses both physical and psychological needs.